Prioritizing Factors Affecting Women\'s Health and Ways to Promote: Using the Hierarchical Analysis Process - Msoomeh Erfani Khanghahi; soodabeh Tayeri (Tehran University of Medical Sciences, 2019)
Background: Womenchr('39')s health has a broad concept that various biological, social, political, economic and environmental factors affect it. This study aimed to prioritize the factors affecting womenchr('39')s health promotion, provide a model for decision making and choose the best option for decision makers and health system planners to achieve the goal of promoting womenchr('39')s health.   Materials and Methods: In this descriptive-analytical study, the factors affecting womenchr('39')s health were extracted based on theoretical background and Farmehrchr('39')s conceptual model. Then, the points of view of five womenchr('39')s health experts on the criteria and options of the model were collected and analyzed using paired comparison tables and Likert measure, and analyzed according to the hierarchical decision-making process. After analyzing the experts chr('39')opinion individually, two methods of computing the geometric meanings and the expertschr('39') opinions were combined and the priorities were determined based on group views. The Excel software was utilized to perform the calculations.   Results: Among the four main factors, priorities included the individual factors (subcategory of lifestyle), family factors (family relationships) and underlying factors (attitudes and beliefs). In the first level of decision making related to intervention methods in womenchr('39')s health promotion, the multidisciplinary approach was determined; and in the second level of decision-making related to health management, the partnership of governmental and nongovernmental organizations established in the first priority.   Conclusion: Based on study results, designing and planning interventions with the prioritization of individual, family and infrastructure factors using multi-disciplinary approach and participation of governmental and nongovernmental organizations for promoting womenchr('39')s health are recommended.